2021
DOI: 10.3390/biology10080737
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase Mutation Exacerbated High-Fat-Diet-Induced Nonalcoholic Fatty Liver Disease with Gut Microbiota Remodeling in Male Mice

Abstract: Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is a critical enzyme involved in ethanol clearance in acetaldehyde metabolism and plays a key role in protecting the liver. The ALDH2*2 mutation causes a significant decrease in acetaldehyde scavenging capacity, leading to the accumulation of acetaldehyde after consuming alcohol. The prevalence of the ALDH2*2 variant is in 45% of Taiwanese individuals. ALDH2 reportedly has protective properties on myocardial damage, stroke, and diabetic retina damage. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…A recent study reported that ALDH2 mutant mice showed obesity-related insulin resistance, which affected the diversity of gut microbiota, decreased the abundance of Actinobacteria, and increased Deferribacteres [ 20 ]. These results suggest that ALDH2 affects obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that ALDH2 mutant mice showed obesity-related insulin resistance, which affected the diversity of gut microbiota, decreased the abundance of Actinobacteria, and increased Deferribacteres [ 20 ]. These results suggest that ALDH2 affects obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol exposure to ALDH2-knockout mice results in greater mitochondrial dysfunction [ 53 ], and ALDH2 overexpression has been shown to attenuate alcohol-induced cardiac dysfunction [ 54 ]. In addition, ALDH2 has also been shown to ameliorate HF diet-induced cardiomyopathy as well [ 55 ], and ALDH2-mutant mice with lower ALDH2 activity fed a HF diet exhibit greater metabolic syndrome and cardiac dysfunction [ 56 , 57 ]. Thus, the reduction in ALDH2 may be a factor contributing to the increased oxidative stress and diminished electron transport chain complex activity in mice exposed to HF and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that there was a female-specific negative association between the intake frequencies of soy products (natto & soy, tofu, soy milk) and BMI. Genistein, which is one of the isoflavones that is abundant in soybeans, has a reported estrogen-like effect [ 41 , 42 , 43 ]. Because estrogen decreases visceral fat accumulation via estrogen receptors [ 44 ], menopausal women have increased visceral fat [ 45 ].…”
Section: Discussionmentioning
confidence: 99%